Synthesis of New 1,3‐Dioxepin Derivatives - KABAPINAR, FİLİZ (My University, 1995)
Using cis‐2‐buten‐1,4‐diol and mono and dicarbonyl compounds eleven new 4,7‐dihydro‐1,3‐dioxepin derivatives were synthesized. Structures were proved by spectroscopic methods. Copyright © 1995 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim